Penggunaan Media Pembelajaran Yang Kreatif dalam Desain Pembelajaran Anak Usia Dini - Susanti Susanti; Ade S Anhar (Jurnal Inovasi Pendidikan Dasar dan Menengah, 2025)
Early childhood education is the foundational stage in shaping children's character, intelligence, and social skills. Therefore, the learning process at this stage must be designed to align with the developmental needs and characteristics of young learners. One of the most essential aspects that can enhance learning effectiveness is the use of creative learning media. Creative learning media go beyond mere visual or audio aids they involve innovative and engaging approaches that stimulate cognitive, affective, and psychomotor development. This article aims to explore the importance of using creative learning media in designing learning experiences for early childhood and how such media influence children’s engagement and understanding of learning content. The method used in this study is a literature review, analyzing various relevant journals, books, and scientific articles. The findings indicate that creative media such as hand puppets, educational games, interactive videos, natural materials, and simple digital tools can significantly increase children’s learning enthusiasm, extend attention span, and support social interaction. Moreover, the teacher's role in selecting or creating appropriate media plays a critical part in the success of the learning design. This study concludes that the use of creative learning media is essential in designing engaging, enjoyable, and meaningful learning experiences for early childhood education. It also serves as an effective bridge between the child's world of play and the world of structured learning